Regulation of glycolysis in brown adipocytes by HIF-1α - Basse, Astrid L. (Sci Rep, 2017)
Brown adipose tissue takes up large amounts of glucose during cold exposure in mice and humans. Here we report an induction of glucose transporter 1 expression and increased expression of several glycolytic enzymes in brown adipose tissue from cold-exposed mice. Accordingly, these genes were also induced after β-adrenergic activation of cultured brown adipocytes, concomitant with accumulation of hypoxia inducible factor-1α (HIF-1α) protein levels. HIF-1α accumulation was dependent on uncoupling protein 1 and generation of mitochondrial reactive oxygen species. Expression of key glycolytic enzymes was reduced after knockdown of HIF-1α in mature brown adipocytes. Glucose consumption, lactate export and glycolytic capacity were reduced in brown adipocytes depleted of Hif-1α. Finally, we observed a decreased β-adrenergically induced oxygen consumption in Hif-1α knockdown adipocytes cultured in medium with glucose as the only exogenously added fuel. These data suggest that HIF-1α-dependent regulation of glycolysis is necessary for maximum glucose metabolism in brown adipocytes.